The Importance of Religious Provision in the Development of Elementary School Age Children at SDIT Solok - Ririn Septya Yunita; Afrahamiryano (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2024)
Development is a process of increasing maturity, thinking and psychological functions in humans. Where these changes are qualitative in nature which refers to changes in typical characteristics towards more advanced ones which will lead to the achievement of new abilities and characteristics. One of the important aspects to help the development process towards a better direction is the cultivation of religious values. Where religion will have a positive impact on the next stage of development. By providing religious education to elementary school-aged children, it is hoped that children will be able to prepare themselves according to existing religious values. The purpose of this article is to find out how important religious training is for elementary school-aged children in carrying out the next stages of development.